Efektivitas Penggunaan Simulasi Komputer Dalam Pembelajaran Fisika - Maulana, Luhfi; Ramadhan, M.Rizky; Irwa, Khairun; Nasution, Adelyna Oktavia (Bahasa Indonesia, 2025)
This study investigates the impact of the use of computer simulation on students' physics learning outcomes. Using experimental methods, this study compares the learning outcomes of students who use computer simulations with students who use conventional methods. The results showed that students who used computer simulation had a significant and higher improvement in learning outcomes compared to students who used conventional methods. The study also found that computer simulations can increase students' motivation and interest in learning. The results of this study show that computer simulation can be an effective alternative learning method in improving students' physics learning outcomes. that students who used computer simulation had a significant and higher improvement in learning outcomes compared to students who used conventional methods. The study also found that computer simulations can increase students' motivation and interest in learning. The results of this study show that computer simulation can be an effective alternative learning method in improving students' physics learning outcomes.